Identifikasi Keanekaragaman Jenis Makrofungi di Kampus Universitas Sebelas Maret, Surakarta - Diharjo, Dewi; Nurmiyati, Nurmiyati (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2022)
Cryptogamae is a group of lower plants that reproduce using spores. One of the lower plants is macrofungi. Macrofungi are lignocellulosic degrading organisms that live in humid places with a fairly wide distribution pattern in the area of Sebelas Maret University, Surakarta. This study aims to determine the types of macrofungiin the area of Universitas Sebelas Maret by using the exploration method. Sampling was carried out evenly in the Sebelas Maret University campus area. The results showed that there were 27 species of marofungi from 2 divisions, namely the division Basidiomycota and Ascomycota. In the Basidiomycota division, there were 24 species consisting of 5 orders (Auriculariales, Boletales, Agaricales, Polyporales, Geastrales) and 13 families. Meanwhile, in the Ascomycota division, there were 3 species, namely Daldinia concentrica, Xylaria apiculata and Xylaria polymorpha. The results of this study indicate that the Sebelas Maret University campus environment has a very high diversity of macrofungi.